ECT9 condensates with ECT1 and regulates plant immunity - Wang, Hui; Niu, Ruixia; Zhou, Yulu; Tang, Zhijuan; Xu, Guoyong; Zhou, Guilong (Frontiers in Plant Science, 2023)
Mounting efficient defense requires RNA binding proteins (RBPs) to secure immune mRNAs transcription, splicing, export, translation, storage, and degradation. These RBPs usually have multiple family members, leaving a question about how they coordinate with each other in conferring cellular functions. Here, we show that an Arabidopsis YTH family member EVOLUTIONARILY CONSERVED C-TERMINAL REGION 9 (ECT9) provides condensation capability to its homolog ECT1 and redundantly controls immune responses. By screening 13 YTH family members, we discover that only ECT9 forms condensates which decrease after treatment with the critical immune signal, salicylic acid (SA). ECT1 cannot form condensates solely but can be recruited to ECT9 condensates in vivo and in vitro. We find that the ect1/9 double mutant but not the single mutant shows elevated immune responses to the avirulent pathogen. Our results suggest that co-condensation constitutes a strategy for RBP family members to confer redundant functions.